19th - Early 20th Centuries Influence of European Architectural Styles on Central Asian Architecture (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article analyzes the influence of European culture on the territory of Central Asia, the formation of new architectural styles in public buildings in connection with the rise of economic and cultural development in the regions of Samarkand, Tashkent and Bukhara. The article also examines the use of traditional elements of national architecture in public buildings and structures built by Russian architects in European styles using examples.